2022
DOI: 10.3390/nu14051089
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium as an Important Factor in the Pathogenesis and Treatment of Migraine—From Theory to Practice

Abstract: So far, no coherent and convincing theory has been developed to fully explain the pathogenesis of migraine, although many researchers and experts emphasize its association with spreading cortical depression, oxidative stress, vascular changes, nervous excitement, neurotransmitter release, and electrolyte disturbances. The contribution of magnesium deficiency to the induction of cortical depression or abnormal glutamatergic neurotransmission is a likely mechanism of the magnesium–migraine relationship. Hence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 67 publications
0
11
0
3
Order By: Relevance
“…Migraine may be associated with electrolyte disturbances, and magnesium deficiency may induce migraine by affecting cortical inhibition or leading to abnormalities in glutamatergic neurotransmission, which is seen as a potential mechanism for the magnesium-migraine association ( 53 ). Magnesium is involved in the regulation of the nervous system through multiple pathways, not only regulating vasodilatation by affecting mitochondrial metabolism, neurotransmitter release, and substance P release, but also attenuating neuroinflammation by inhibiting the nuclear factor κB pathway in pro-inflammatory cells ( 54 , 55 ).…”
Section: Applications and Research Evidences Of Cat In Migraine Manag...mentioning
confidence: 99%
“…Migraine may be associated with electrolyte disturbances, and magnesium deficiency may induce migraine by affecting cortical inhibition or leading to abnormalities in glutamatergic neurotransmission, which is seen as a potential mechanism for the magnesium-migraine association ( 53 ). Magnesium is involved in the regulation of the nervous system through multiple pathways, not only regulating vasodilatation by affecting mitochondrial metabolism, neurotransmitter release, and substance P release, but also attenuating neuroinflammation by inhibiting the nuclear factor κB pathway in pro-inflammatory cells ( 54 , 55 ).…”
Section: Applications and Research Evidences Of Cat In Migraine Manag...mentioning
confidence: 99%
“…Only a few studies have demonstrated a reduction in the length and severity of migraine headaches. In dysbiosis, magnesium serves as an adjuvant therapy ( Table 3 ) [ 66 , 67 ].…”
Section: How To Modify the Gut Microbiotamentioning
confidence: 99%
“…Unfortunately, the strength of evidence supporting oral magnesium supplementation is still limited [467]. But most recently there are some promising studies indicating that supplementary magnesium might be beneficial, especially in pediatric but also in adult patients [468][469][470]. 39 Coenzyme Q10 (Ubiquinone-10) was discovered in 1957 and first isolated from bovine hearts by Frederick L. Crane (1925Crane ( -2016 at the University of Wisconsin [460].…”
Section: Magnesiummentioning
confidence: 99%